CONSIDERATIONS ON THE COORDINATION OF PREVENTIVE RESTRUCTURING MEASURES INTRODUCED BY DIRECTIVE (EU) 2019/1023 OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL OF 20 JUNE 2019 ON PREVENTIVE RESTRUCTURING FRAMEWORKS, ON DISCHARGE OF DEBT AND DISQUALIFICATIONS, AND ON MEASURES TO INCREASE THE EFFICIENCY OF PROCEDURES CONCERNING RESTRUCTURING, INSOLVENCY AND DISCHARGE OF DEBT, AND AMENDING DIRECTIVE (EU) 2017/1132 (DIRECTIVE ON RESTRUCTURING AND INSOLVENCY) - Vasile NEMEȘ; Gabriela FIERBINȚEANU (Challenges of the Knowledge Society)
Preventive solutions are a growing trend in insolvency law and approaches that have the aim of saving the companies which are still economically viable are a benefit to the economy. Differences between Member States in relation to procedures concerning restructuring, insolvency and discharge of debt generate additional costs for investors and also lead to uneven conditions for access to credit and to uneven recovery rates. A higher degree of harmonisation in the field of restructuring, insolvency, discharge of debt and disqualifications is thus indispensable for a well-functioning internal market in general and for a working Capital Markets Union in particular. These are only some of the results of the reflection determining the initiative for a new legal framework, as introduced by the Directive (EU) 2019/1023 of 20 June 2019 on preventive restructuring frameworks, on discharge of debt and disqualifications, and on measures to increase the efficiency of procedures concerning restructuring, insolvency and discharge of debt, and amending Directive (EU) 2017/1132 (Directive on restructuring and insolvency). This paper does not aim to offer solutions or to critically analyse the level of ambition of the Directive, but only to provide an examination of the national frameworks in articulation with the new instrument introduced at Union level, indicating new trends foreseen by its provisions and preliminary directions for reflection in the transposition process.